(untitled) (Analysis in Theory and Applications, 2016)
Let T be the singular integral operator with variable kernel, T^* be the adjoint of T and T^ be the pseudo-adjoint of T. Let T_1T_2 be the product of T_1 and T_2, T_1° T_2 be the pseudo product of T_1 and T_2. In this paper, we establish the boundedness for commutators of these operators and the fractional differentiation operator D^γ on the weighted Morrey spaces.